Age or environmental radiation dose rate: Which is more correlated with cancer incidence rates in the Republic of Korea? - Joo, Han Young; Kim, Jae Wook; Jeong, So Yun; Choi, Jin Sik; Moon, Joo Hyun (Nuclear engineering and technology, 2022)
Our study adopted a big data analysis approach to determine whether there was a significant relationship between environmental radiation dose rates or age and cancer incidence rates in the Republic of Korea. The data for this analysis included environmental radiation dose rates, number of cancer patients, and age distributions of the residents from 2009 to 2016 in the administrative districts where environmental radiation monitoring posts were located. For this analysis, the environmental radiation dose rates were obtained from 171 monitoring posts located in 113 elementary administrative districts in the Republic of Korea. The number of cancer patients and the age distributions were obtained from the Central Cancer Information Center of the National Cancer Center of Korea and the Ministry of the Interior and Safety, respectively. Our findings indicated that there was no statistically significant relationship between the environmental radiation dose rate and the cancer incidence rate. However, age had a considerable influence on the cancer incidence rate of the monitored regions.